COMPARATIVE ANALYSIS OF TAP, BOREHOLE, WELL AND PACKAGE WATER IN GOMBE METROPOLIS - Saidu, Haruna; Muhammed, Kabiru; Garkuwa A., Nuru; Muhammed, Ishaku; Aliyu, Abubakar Sadiq; Abdullahi, Ayna’u (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Water is very essential substances for human existence. It is widely used for industrial and domestic usage. However, increase in wastewater discharge mainly from industrial activities has recently increases the level of water pollution. A report from world health organization (WHO) estimated that several individual die annually due to the comsumption of polluted water. Therefore comparative analysis of some selected water sample was carried in the present study with aim of providing quality condition of water fit for human consumption. Tap, borehole, packet and well water were collected from different location in Gombe metropolis and their physical chemistry and viable cell count were quantified according to the standard method of WHO. The result of the study shows that, physicochemical parameters of the selected water sample agree with the acceptable standard of WHO. The microbial total viable count was found to exceed the standard limit of 1 × 102 cfu/mL for water. The study, a comparative analysis of water sample from different sources can be an effective step to be adopted by water management bodies in order to provide healthy drinking water especially to areas of limited sanitary inspection in Gombe metropolis.